Ultrasound diagnosis of varicocele in the adolescent: Our experience from Benin - Michel A Fiogbe; Maroufou J Alao; Olivier Biaou; Séraphin A Gbenou; Patricia Yekpe; Roger Sossou; Serge C Metchihoungbe (Wolters Kluwer Medknow Publications, 2013)
Background: The diagnosis of varicocèle is clinical. In order to improve diagnosis of varicocele, we compared the clinical with the ultrasound findings in schoolboys with the condition. This is because the conditions can affect testicular growth. Patients and Methods: It was a cross-sectional, descriptive study of schoolboys aged from 10 to 19 years who had varicocele. Among 2724 boys examined, 149 had varicocele and only 81 had scrotal (18 with Doppler) and renal ultrasound examination. Results: Among the 81 adolescents who were clinically diagnosed with varicocele and also with the aid of ultrasound scan, 25, 36 and 20 had grade 1, 2 and 3, respectively. Testicular hypotrophy (TH) was clinically noticed in 17 cases. At ultrasonography, varicocele was bilateral in 87.66% and unilateral in 12.34% (P = 0.01) with 32 adolescents (39.51%) showing TH compared with 20.99% being diagnosed with TH using clinical examination alone (P = 0.01). In 50 schoolboys (61.73%) with unilateral varicocele, a subclinical type was discovered at other side. Renal ultrasound revealed abnormalities in 4.93% of cases. Doppler ultrasound helped in finding varicoceles along the top edge of the testis (n = 15) and under tunica albuginea (n = 3). Conclusion: TH due to varicocele is better studied by ultrasound.